Cardiac motion simulation in cadavers and carotid artery longitudinal wall behaviour - Stevens, Kailey (University of Waterloo, 2023)
Carotid artery longitudinal motion (CALM) is a bidirectional, multiphasic motion of the intima-media complex of the common carotid artery (CCA) wall. This motion has exhibited changes with aging, elevated cardiovascular disease risk, and various diseased conditions. Understanding the determinants of this motion may position CALM as a diagnostic tool for arterial health. Retrograde wall displacement is the hallmark feature of this phenomenon and represents movement of the arterial wall in the opposite direction of blood flow, but its etiology remains undiscovered. While retrograde motion has been proposed to result from cardiac contraction due to ventricular-vascular coupling of the arterial tree and the heart, separating hemodynamic influences from cardiac contraction is not possible in vivo. This study explores simulated cardiac contraction in cadavers and the influence of longitudinal prestretch and material stiffness on carotid artery longitudinal wall behavior. Eight cadavers (5 males, 85 ± 7 years (n = 7) in addition to one 19-year-old donor (n = 1)) underwent a dissection and tissue testing protocol. The dissection protocol examined the relationship between caudal force application at the ascending aorta and resulting CCA longitudinal wall displacement. A repeated measures correlation revealed a moderate negative correlation for applied force and wall displacement (r = -0.68, p < 0.001, 95%CI [-0.76, -0.60]). Displacement was estimated for a standardized force of 6 N for each donor and artery. Longitudinal prestretch did not influence displacement at 6 N (rLCCA = -0.13, p = 0.78; rRCCA = -0.63, p = 0.13). There was no significant relationship found between displacement at 6 N and either longitudinal strain [rLCCA = -0.72, p = 0.070; rRCCA = -0.27, p = 0.56] or elastic modulus at 35 kPa [rLCCA = 0.50, p = 0.25; rRCCA = 0.29, p = 0.53] for either side. Circumferential strain [rLCCA = -0.068, p = 0.14; rRCCA = 0.13, p = 0.79] and elastic modulus [rLCCA = 0.58, p = 0.23; rRCCA = -0.31, p = 0.50] were not related with displacement at 6 N for either side. Differences between the LCCA and RCCA were identified for the slope of force-displacement line of best fit [p = 0.0347, Cohen’s d = 1.17, n = 6], longitudinal strain at 35 kPa [p = 0.020, Cohen’s d = 1.37, n = 6], and circumferential elastic modulus at 35 kPa [p = 0.018, Cohen’s d = 1.72, n = 5], suggesting increased wall displacement in the LCCA and increased stiffness of the RCCA. Our findings suggest that cardiac contraction is a primary determinant of CALM, and cardiac imaging should be conducted with CALM imaging in future studies to contextualize differences in motion between individuals and across acute interventions. Due to anatomical branching differences, images should be taken on the LCCA for a more direct influence from cardiac contraction. Our results support the ventricular-vascular coupling theory for retrograde motion in CALM and demonstrate greater wall displacement in the LCCA compared to the RCCA.